The Influence of Content Marketing and Innovation Speed Toward Repurchase Intention Fashion MSME On Instagram (Case Study of Erigo Store): Pengaruh Konten Pemasaran dan Kecepatan Inovasi terhadap Niat Membeli Kembali UMKM Fashion Di Instagram (Studi Kasus pada Erigo Store) - Putri Mayang Zivi; Fortuna Zain Hamid; Anwar Mustofa (Administratif Profesional, 2022)
The purpose of this study is to determine and analyze the partial and simultaneous between content marketing and innovation speed toward repurchase intention Fashion MSME On Instagram (Case Study of Erigostore). In addition, this research is expected to be a consideration for companies or fashion MSME to increase Repurchase Intention. This research is included in casual associative research with a quantitative approach with a sample calculation using the slovin formula. So the number of samples is 100 respondents and in the sampling technique used using purposive sampling. A literature review and quesionnaire distribution were used to collect data. The validity and reliability test are used in instrument testing, white the data analysis method employs multiple linear regression analysis, T test, F test, and the coefficient of determination R2. The regression equation Model Y = 10,806 + 0,342X1 + 0,447X2 + e is worth to use. Based on the results of the partial correlation, the content marketing variable (X1) has an influence on repurchase intention (Y) of 50,69%, while the innovation speed variable (X2) has an influence on repurchase intention (Y) of 47,74%. Based on the results of the coefficient of determination R2 of 53,1% repurchase intention is influenced by content marketing and innovation speed, while the remaining 46,9% is influenced by other variables not discussed in this study such as viral marketing, celebrity endorser, online customer review, etc. The results of this study indicate that there is an effect of content marketing and innovation speed on repurchase intention simultaneously (F test), and the effect of content marketing and innovation speed on repurchase intention partially (T test) based on hypothesis testing. Keywords: Content Marketing, Innovation Speed, Repurchase Intention